Using natural resources for development: why has it proven so difficult? - Venables, A (University of Oxford, 2016)
Developing economies have found it hard to use natural resource wealth to improve their economic performance. Utilising resource endowments is a multi-stage economic and political problem that requires private investment to discover and extract the resource, fiscal regimes to capture revenue, judicious spending and investment decisions, and policies to manage volatility and mitigate adverse impacts on the rest of the economy. Experience is mixed, with some successes (such as Botswana and Malaysia) and more failures. This paper reviews the challenges that are faced in successfully managing resource wealth, the evidence on country performance, and the reasons for disappointing results.